Role of HK2 in the Enzootic Cycle of Borrelia burgdorferi - Liu, Qiang; Xu, Haijun; Zhang, Yan; Yang, Jing; Du, Jimei; Zhou, Yan; Yang, X. Frank; Lou, Yongliang (Frontiers in Medicine, 2020)
The two-component response regulator Rrp2 is a key activator controlling the production of numerous virulence factors of Borrelia burgdorferi, the Lyme disease pathogen. Previously it was showed that the cognate histidine kinase HK2 is not required for Rrp2 activation in vitro, nor for mammalian infection upon needle inoculation, raising the question whether HK2 has any role in the enzootic cycle of B. burgdorferi. In this study, we showed that HK2 is not required for spirochetal survival in the tick vector. When fed on naive mice, the hk2 mutant had reduced infectivity through the route of tick bite, suggesting that the spirochetes lacking HK2 had a disadvantage in the enzootic cycle. Furthermore, overexpression of hk2 reduced the level of Rrp2 phosphorylation, suggesting that HK2 can functions as a phosphatase to dephosphorylate Rrp2. Strains with overexpression of hk2 impaired the expression of RpoN regulon whose activation is dependent on Rrp2 phosphorylation and activation, and had reduced infectivity in mice. Taken together, these results demonstrate that although HK2 does not play an essential role in Rrp2 activation, it is important for the optimal fitness of B. burgdorferi in the enzootic cycle.